Challenges and opportunities on vegetable oils derived systems for biomedical applications - Ribeiro, Ana R. (2022)
Vegetable oils have been suggested in polymer science as an environmentally friendly feedstock existing in abundance in nature, with worldwide availability and low cost. Although they have been widely explored as building blocks for polymers synthesis, their functional roles as owners of potent biomolecules are less unexplored. Their ancient biomolecules support natural biological roles such as antioxidant, antibacterial, anti-inflammatory, and anti-tumor properties, which are considered a great promise for biomedical proposes. This comprehensive review provides an overview of grape, soybean, castor, sesame, olive vegetable oils where their native anti-inflammatory, anti-tumor, antioxidant, and antibacterial biological compounds bring health benefits that can be translated to the biomedical field. These plant oils are considered the most relevant for the molecular design of functional and high-performance biomaterials that can contribute to the reduction of carbon footprint. The representative examples of vegetable oil-derived biomaterials, their main composition, shape, and the processing technology will be covered and innovative strategies toward the development of new multifunctional polymeric materials for pharmacological patches, wound healing devices, drug carriers, and scaffolds for tissue engineering applications will be discussed.